Import protection, business cycles, and exchange rates: Evidence from the great recession - Chad P. Bown; Meredith A. Crowley (Federal Reserve Bank of Chicago, 2011)
This paper uses highly detailed, quarterly data for five major industrialized economies to estimate the impact of macroeconomic fluctuations on import protection policies over 1988:Q1 - 2010:Q4. First, estimates on a pre-Great Recession sample of data provide evidence of two key relationships. We confirm that appreciations in bilateral real exchange rates lead to substantial increases in antidumping and related forms of import protection: e.g., a 4 percent appreciation results in 60 - 90 percent more products being subject to import protection. We also provide evidence of a previously overlooked result that policy-imposing countries historically imposed such bilateral import restrictions on trading partners that were going through periods of weak economic growth. Second, we use the model to then provide the first estimates that link macroeconomic fluctuations to a change in policy-imposing behavior during the Great Recession so as to explain the realized protectionist response. During the Great Recession, the US and other policyimposing economies became less responsive to exchange rate appreciations. Furthermore, the US and other economies switched from their historical behavior and shifted implementing new import protection away from those trading partners that were contracting and toward those experiencing economic growth. In a final exercise, we document how the model's estimates imply that a 9 - 20 percent appreciation of China's real exchange rate vis-a-vis the US dollar during the sample period would allow for China's exporters to have received the average import protection treatment under antidumping that the US imposed against other countries.
Keywords: F13; 330; antidumping; safeguards; US; Canada; EU; Korea; Australia; China; Konjunktur; Antidumping; Protektionismus; USA; EU-Staaten; Südkorea; Australien; Kanada